Nanocomposite coatings and pseudo-alloys - Pedchenko, Dmytro; Kniazieva, Hanna; Kniaziev, Sergey (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper explores modern approaches to the fabrication of thin nanocoatings and pseudo-alloys, particularly those based on the tungsten–copper (W–Cu) system, using vacuum-plasma deposition technologies. It is shown that non-equilibrium deposition conditions contribute to the formation of metastable structures with enhanced physical and mechanical properties. The main stages of thin-film formation in vacuum are analyzed, as well as the influence of technological parameters on the morphology, composition, and characteristics of the coatings. The properties of W–Cu pseudo-alloys and their potential fields of application are also discussed.
Keywords: pseudo-alloys; thin films (coatings); W–Cu composites